2023
DOI: 10.3847/1538-4365/aceb62
|View full text |Cite
|
Sign up to set email alerts
|

A Coronal Mass Ejection Source Region Catalog and Their Associated Properties

Satabdwa Majumdar,
Ritesh Patel,
Vaibhav Pant
et al.

Abstract: The primary objective of this study is to connect coronal mass ejections (CMEs) to their source regions, primarily to create a CME source region catalog, and secondarily to probe the influence that the source regions have on the different statistical properties of CMEs. We create a source region catalog for 3327 CMEs from 1998 to 2017, thus capturing the different phases of cycles 23 and 24. The identified source regions are segregated into three classes—active regions, prominence eruptions, and active promine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…K-Cor being a ground-based facility, data acquisition is restricted to only a few hours during the day, which further constrained the event selection. To identify the source regions of the CMEs, we follow the methodology of Pant et al (2021) and Majumdar et al (2023) on the SWAP and AIA images, and the identified source regions are shown in Table 1. The ARs are the usual flaring regions showing bright emission in extremeultraviolet wavelengths, the prominences that erupt from the quiet Sun regions are denoted as PEs, and the prominences whose footpoints are rooted in an AR are classified as APs.…”
Section: Working Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…K-Cor being a ground-based facility, data acquisition is restricted to only a few hours during the day, which further constrained the event selection. To identify the source regions of the CMEs, we follow the methodology of Pant et al (2021) and Majumdar et al (2023) on the SWAP and AIA images, and the identified source regions are shown in Table 1. The ARs are the usual flaring regions showing bright emission in extremeultraviolet wavelengths, the prominences that erupt from the quiet Sun regions are denoted as PEs, and the prominences whose footpoints are rooted in an AR are classified as APs.…”
Section: Working Methodsmentioning
confidence: 99%
“…The impulsive CMEs tend to originate from the active regions (ARs) on the Sun, while the gradual CMEs are connected to erupting prominences. This distinction is reflected in different aspects of the kinematics of these CMEs (see Majumdar et al 2021;Pant et al 2021) and in various statistical properties, as recently pointed out based on a CME source region catalog by Majumdar et al (2023). Hence, whether any difference in the velocity dispersion is seen for impulsive and gradual CMEs is worth studying.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, the HCS is oriented along the Parker spiral field on average at 1 au (e.g., Liou & Wu 2021). Thus interactions of the HCS with outgoing solar transient events, such as CMEs, are likely, especially when most CMEs take place at low latitudes (Majumdar et al 2023). When an observer is located at a different magnetic hemisphere from the source of SEPs, i.e., separated by the HCS, reduced or no SEP flux can result if the HCS can inhibit crossings of SEPs.…”
Section: Introductionmentioning
confidence: 99%